Pengaruh Lama Pemanasan Terhadap Karakteristik Kristal Kalsium dari Limbah Cangkang Kerang - Fitri Afriani; Mustari Mustari; Yuant Tiandho (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2018)
The high number of tin mining in the Bangka Belitung Islands leaves a number of problems such as unused land after tin mining. Whereas on the other side, the post tin mining areas can be used as a source of water reserves although additional treatment is needed because it is feared contain heavy metals. Calcium oxide is a compound that can be used to coagulate dispersed pollutants in water so that it can be used to improve the quality of water stored in the post tin mining area. One of the most abundant sources of calcium in the Bangka Belitung Islands comes from wasted cockle shell. Through a heating process at temperatures of about 700Â°C calcium carbonate in the wasted cockle shell will begin to decompose into calcium oxide. Based on the results obtained have known that the longer the heating process then the decomposition process of calcium carbonate more and more occur. Keywords: Rietveld, calcium crystal, heat treatment.